The block planning approach for continuous time-based dynamic lot sizing and scheduling - Hans-Otto Günther (Business Research, 2014)
This paper calls for a change in paradigm in lot sizing and scheduling. Traditionally, a discrete time scale is chosen to model lot sizing and scheduling. As an alternative, the so-called block planning concept is proposed which is based on a continuous representation of time. A mixed-integer linear optimization model is presented that determines the size and the time phasing of the individual production lots in a single-stage production system under the objective of minimizing the makespan. The modelling approach presented here assumes the grouping of product variants into setup families and the production of product variants within a family in a pre-defined sequence. Numerical results demonstrate the practicability of this approach under experimental conditions which reflect typical settings from a leading company in the European beverage industry.
Keywords: C61; M11; 330; Lot sizing and scheduling; Block planning; Mixed-integer linear programming